Demographics and FDI: Lessons from China's one-child policy - John B. Donaldson; Christos Koulovatianos; Jian Li; Rajnish Mehra (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
Following the introduction of the one-child policy in China, the capital-labor (K/L) ratio of China increased relative to that of India, and, simultaneously, FDI inflows relative to GDP for China versus India declined. These observations are explained in the context of a simple neoclassical OLG paradigm. The adjustment mechanism works as follows: the reduction in the growth rate of the (urban) labor force due to the one-child policy permanently increases the capital per worker inherited from the previous generation. The resulting increase in China's (domestic K)/L thus "crowds out" the need for FDI in China relative to India. Our paper is a contribution to the nascent literature exploring demographic transitions and their effects on FDI flows.
urn:nbn:de:hebis:30:3-480187
Keywords: F11; F21; J11; O11; E13; 330; Lucas paradox; capital-labor ratio; FDI-intensity; one-child policy